1978
DOI: 10.1152/jappl.1978.44.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of positive end-expiratory pressure in dogs

Abstract: Our purpose was to reexamine the relationship of the fall in cardiac output and blood pressure which occurs during positive end-expiratory pressure (PEEP) to changes in transmural right atrial and left atrial filling pressures. Closed-chest dogs, half with pulmonary edema, were studied during spontaneous breathing and inspiratory positive-pressure breathing (IPPB) with 0-15 cmH2O PEEP. Mean esophageal pressure accurately reflected changes in pericardial pressure and was used to estimate extracardiac pressure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…DLCO computed per unit lung volume decreased with increasing levels of PEEP suggesting creation of lung zones in which alveolar pressure exceeded arterial pressure, as would be expected with the application of PEEP. The decrement in pulmonary capillary blood flow with PEEP is similar to that reported by us and others (3, 4,9,12) and the decrement in Q, with oleic acid infusion and PEEP is similar to previously reported values from our laboratory in dogs (9). These data suggest that the rebreathing volumes used and airway pressures developed during the rebreathing maneuver in the present study were not excessive.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…DLCO computed per unit lung volume decreased with increasing levels of PEEP suggesting creation of lung zones in which alveolar pressure exceeded arterial pressure, as would be expected with the application of PEEP. The decrement in pulmonary capillary blood flow with PEEP is similar to that reported by us and others (3, 4,9,12) and the decrement in Q, with oleic acid infusion and PEEP is similar to previously reported values from our laboratory in dogs (9). These data suggest that the rebreathing volumes used and airway pressures developed during the rebreathing maneuver in the present study were not excessive.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of PEEP on normal lungs was predictable and similar to that found in larger animals, i.e. an increase in lung volume and decrease in pulmonary capillary blood flow (4,9,12). DLCO computed per unit lung volume decreased with increasing levels of PEEP suggesting creation of lung zones in which alveolar pressure exceeded arterial pressure, as would be expected with the application of PEEP.…”
Section: Discussionsupporting
confidence: 73%
“…PEEP generally decreases cardiac output, and the cause of this decrease has been the focus of much research over the past decade. A few studies in intact animals or humans have suggested impairment of cardiac contractility on PEEP [48,50]. MANNY et al [51] perfused an isolated heart with blood from a support dog.…”
Section: Steady-state Effects Positive End-expiratory Pressure and Comentioning
confidence: 99%
“…If this were true, the effective or transmural filling pressure of the right atrium (right atrial pressure minus pleural pressure) would be expected to decrease during CPPV. However, several investigators have reported that transmural right and left atrial pressures, measured rel- ative to lateral pleural or esophageal pressure, do not decrease, but stay the same or actually increase during CPPV (Scharf et al, 1977;Zarins et al, 1977;Cassidy et al, 1978). This suggests that decreased venous return is not the primary factor producing the decrease in cardiac output.…”
Section: Circ Res 46: 125-132 1980mentioning
confidence: 99%